Alzheimer's disease diagnostic progression is associated with cerebrovascular disease and neuroinflammation in adults with Down syndrome - Edwards, Natalie C.; Lao, Patrick J.; Alshikho, Mohamad J.; Ericsson, Olivia M.; Rizvi, Batool; Petersen, Melissa E.; O'Bryant, Sid; Flores-Aguilar, Lisi; Simoes, Sabrina; Mapstone, Mark; Tudorascu, Dana L.; Janelidze, Shorena; et al. (Alzheimer's and Dementia, 2025)
INTRODUCTION: Despite having few vascular risk factors, people with Down syndrome (DS) have MRI evidence of cerebrovascular disease (CVD) and neuroinflammation that worsens with Alzheimer's disease (AD) severity. We investigated whether markers of CVD and inflammation are associated with AD-related diagnostic progression in people with DS. METHODS: We included 149 participants (mean age [SD] = 44.6 [9]) from the Alzheimer's Biomarkers Consortium–Down Syndrome who had two (n = 24) or three follow-up visits (n = 125). We derived white matter hyperintensity (WMH) volume and plasma biomarker (glial fibrillary acidic protein [GFAP], amyloid beta [Aβ]42/Aβ40, hyperphosphorylated tau-217 [p-tau217], and neurofilament light [NfL]) concentrations at baseline and examined their association with progression in clinical diagnosis. RESULTS: Higher baseline WMH volume and higher GFAP were associated with a greater likelihood of diagnostic progression. Combining WMH and GFAP with p-tau217 improved clinical conversion classification accuracy over AD biomarkers alone. Among individuals with evidence of amyloidosis, both WMH and GFAP were associated with clinical progression. DISCUSSION: In DS, markers of CVD and inflammation are independently and synergistically associated with clinical AD progression. Highlights: Higher baseline white matter hyperintensity (WMH) volume and plasma glial fibrillary acidic protein (GFAP) concentration were associated with a higher likelihood of progressing from cognitively stable to either mild cognitive impairment or clinical Alzheimer's disease in Down syndrome. WMH volume and GFAP concentration discriminated between those who progressed and those who did not. Models including the independent and interactive effects of WMH and GFAP more accurately discriminated between participants who progressed diagnostically from those who did not. Individuals with evidence of amyloid pathology were more likely to progress if they also had elevated WMH or GFAP.
Keywords: Alzheimer's disease progression; biomarker; dementia; white matter hyperintensity